Reflexão acerca do tema tratamento da informação nos anos iniciais de escolarização - MIRANDA, Fernando da Silva (2020)
This Gift Search About Data Processing nsa year Initial TEM The main focus of a part table and graphs , try How Objective To show how the teaching-learning difficulties On the part of tables and graphs , try to base How Research Reports Teachers in the area of the initial year OS Official Documents That are , tHE National Curriculum Parameters (PCN 's ) and the base of Common National Curriculum data BOOKS tHE Didactic . I could come to the conclusion que ATRAVES This research concluded that the teaching-learning problems can be solved in a simple way a SUBJECT So rich To Be Explored By Teachers Working with facts to students everyday bringing paragraph within the classroom matters Causes que tHE students have Interest in Learning and IT Makes Being one adult with autonomy , with the ability to solve problems of his daily life.